Quand l’art public (dé)fait la ville ? - Pauline Guinard (EchoGéo, 2010)
The City of Johannesburg is the first and the only South African city that has implemented a “Public Art Policy” since 2007. This policy fits into a wider urban project thanks to which the City aims at (re)defining itself as a post-Apartheid global city. Public art is conceived as a means to reconcile promotion of economic urban growth with overtaking of the divisions inherited from Apartheid. Nevertheless, in the light of an emblematic case study of one of these artworks, it is shown that public art as promoted by the municipality struggles to free itself from the legacy of Apartheid and to create social interaction into public spaces. Is this difficulty of municipal public art to be more than art in public space a result of the model of public art chosen? Or, more crucially, is this linked with the incompatibility of the goals of the policy?